Implementasi Profetik di Lembaga Pendidikan Tinggi - Zainal Panani; Imam Fuadi; Ahmad Tanzeh; Kojin Kojin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of writing this article is to find out the implementation of prophetics in higher education institutions. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that the importance of education is found in various Islamic literature, especially in the Qur'an as a guide for humans in implementing life and life. The implementation of prophetic in higher education is carried out through a program of instilling character values ​​and developing a grand design for character education adapted to the vision and mission of higher education. Character configuration in the context of the totality of psychological and socio-cultural processes can be grouped into: spiritual and emotional development, intellectual development, physical and kinesthetic development, and affective exercise. and creativity development). The development of education implementation based on prophetic values ​​in higher education is carried out in an integrated manner through three channels, namely: integration in learning, management of departments and study programs, as well as student activities. The steps include design, implementation, evaluation and follow-up which will be developed and implemented in the development of the higher education institution concerned itself.